What is 9/6 minus 6?
Looking for the result of 9/6 - 6? Follow this step-by-step guide to understand how to subtract these two fractions.
How to subtract 9/6 by 6?
- Multiply the numerator of the first term, with the denominator of the second term: 9 × 1 = 9
- Multiply the numerator of the second term, with the denominator of the first term: 6 × 6 = 36
- Subtract both of these results together to form the new numerator: 9 − 36 = -27
- Multiply both denominators together to form the new denominator: 6 × 1 = 6
- Combine the results to get the new fraction: -27/6
- Simplify the fraction (-27/6) by dividing both the numerator and the denominator by their GCD (3):
- -27/3 = -9
- 6/3 = 2
- This gives: -9/2.
The result of subtracting 9/6 and 6/1 is : -9/2 (or -4.5 in its decimal form)